T127. GENDER DIFFERENCES IN CLINICAL PRESENTATION AND ILLICIT SUBSTANCE USE DURING FIRST EPISODE PSYCHOSIS: AN ELECTRONIC CASE REGISTER NATURAL LANGUAGE PROCESSING ANALYSIS. (18th May 2020) - Irving, Jessica; Colling, Craig; Shetty, Hitesh; Pritchard, Megan; Stewart, Robert; Fusar-Poli, Paolo; McGuire, Philip; Patel, Rashmi
Abstract: Background: Gender differences in the clinical presentation of first episode psychosis (FEP) and its relationship to illicit substance use are inconclusive and underexplored. We conducted an electronic health record (EHR) study applying natural language processing (NLP) techniques to investigate gender differences in psychiatric symptoms when controlling for age, ethnicity, and illicit substance use. Methods: Data were extracted from EHRs of 3, 340 people presenting to the South London and Maudsley (SLaM) NHS Trust between April 2007 and March 2017 with FEP. Logistic regression was used to examine gender differences in presentation of 42 psychiatric symptoms, grouped into positive, negative, depressive, mania and disorganisation symptoms. We controlled for age of onset, ethnicity and illicit substance use (cocaine, amphetamine, MDMA or cannabis) and adjusted p-values for multiple comparisons. Results: Patients were predominantly male (62%). Eight symptoms were more prevalent in males (poverty of thought, negative symptoms, social withdrawal, poverty of speech, aggression, grandiosity, paranoia and agitation), and thirteen in females (tearfulness, low energy, reduced appetite, low mood, pressured speech, mood instability, flight of ideas, guilt, mutism, insomnia, poor concentration, tangentiality and elation), before adjustment for age, ethnicity and substance use. Male patients were significantly more likely to experience negative symptoms than females (e.g. poverty of thought, OR 1.85, 95% CI 1.33 to 2.62); female patients showed increased likelihood of depressive and manic symptoms (e.g. tearfulness, 0.30, 0.26 to 0.35). Male patients were significantly more likely to misuse amphetamines, cannabis and cocaine (e.g. cannabis, OR 3.18, 2.75 to 3.70). All significant differences survived controls for age and ethnicity. After adjustment for illicit substance use gender differences in aggression, agitation, paranoia and grandiosity became insignificant (p > 0.05). However, adjustment for illicit substance use resulted in increased strength of gender associations with negative, manic and depression symptoms. Discussion: There are clear gender differences in the clinical presentation of FEP which are modified by exposure to illicit substances. These findings highlight a need to better understand the impact of gender on clinical presentation and treatment outcomes in psychosis, and to ensure that clinicians are aware of how gender differences in presentation could be modified by illicit substance use.